A comprehensive overview of maximum power extraction methods for PV systems. (October 2017) - Kandemir, Ekrem; Cetin, Numan S.; Borekci, Selim
Abstract: The power generated by photovoltaic (PV) system depends on environment irradiance and temperature parameters. Hence, PV panels have nonlinear characteristics. In uniform condition, there is only one maxima point called maximum power point (MPP) where the PV system operates in maximum efficiency. However, in non-uniform condition such as partial shading effects, the PV system presents multiple maxima points on the correspondence P-V curve due to bypass diodes which makes more difficult to estimate global MPP. That is why it makes maximum power point tracking (MPPT) more important for PV systems to operate in maximum efficiency. In the literature, various types of MPPT technique and alternative solutions are used to detect true global MPP point among the other local MPPs. In addition, different PV array topologies, architectures and configurations are proposed to remove local maxima on the P-V curve. In this paper, most popular and used MPPT techniques, PV array configurations, system architectures and circuit topologies are discussed. In this context, this paper provides an overview of the operating principles discusses advantages and disadvantages and makes a general comparison between different solutions of each method.